The challenge posed by the islamic state to the westphalian system in the middle east - Xue, Jianyue (2018)
The Islamic State (IS) is an anti-Westphalian revolutionary state. It seeks to reverse, in the Islamic World, what Martin Wight would describe as a "revolution of loyalties" from religion-based sovereignties to state-based sovereignties from the 1800s onwards. IS wants to revive a united Islamic world order that last existed during the Abbasid Caliphate in the 1200s. IS draws ideological inspiration from thinkers of the Hanbali school of jurisprudence such as Ibn Taymiyya, Abd al-Wahhab, Sayyid Qutb and Abdullah Azzam. Although it fulfills many qualities of a revolutionary state as described by Stephen Walt, IS lacks the power to spread its revolution worldwide. Walt speculates that IS could either become a "normal state" through containment, or be overthrown. This paper argues that despite its weaknesses, IS is likely to continue resisting the Westphalian system in the long run, leading to a protracted struggle. IS' grave violations of international norms, as well as entrenched anti-Westphalian expansionism, make IS and the Westphalian system fundamentally unacceptable to each other.